Pengaruh Gangguan Kecemasan Terhadap Hasil Belajar Siswa di SMK Negeri 1 Makassar - Nuraisyiah, Nuraisyiah; Nurdiana, Nurdiana; Ma'ruf, Muhammad Imam (Universitas Negeri Makassar, 2019)
This study aims to determine the effect of anxiety disorders on student learning outcomes in accounting subjects class XI at SMK Negeri 1 Makassar. This study uses questionnaires and documentation in collecting data. This study uses descriptive percentage analysis, and statistical analysis for statistical analysis of data. Statistical analysis of data includes Simple Linear Regression Analysis, and t-test. The results showed that anxiety disorders on student learning outcomes in class XI accounting subjects at SMK 1 Makassar through nine indicators namely: tense, confused, worried, difficult to concentrate, unable to sleep, heart palpitations, excessive cold sweat, frequent trembling, and Mules' stomach has a negative and significant effect. This means that if students experience anxiety disorders it will reduce student learning outcomes.